2GHz frequency stabilized actively mode-locked fiber laser with piezoelectric tube-based feedback controlsystem - Lam, Huy Quoc (2013)
In this paper, a frequency stabilized actively mode-locked fiber laser with 2 GHz repetition rate is proposed and demonstrated. The feedback control systemutilized for frequency stabilization is based on a piezoelectric tube (PZT) whose size varies withdifferent DC bias strengths. By tightly winding a segment of fiber laser cavity on the PZT, an error signal can be generated by using the output of the laser source to dynamically change the laser cavity length itself and thus the repetition frequency of the output pulse. Transient processfor thefeedback control isexaminedfirst in this paper, followed by an experimental verification, in which a laser pulse train with greatly enhanced frequency stability and significantly reduced phase noise is obtained, regardless of the environmental perturbations. Frequency-stable mode-locked lasers have applications in generation of low-noise microwave and millimetre-wave signals.